SMART CITY THROUGH SMART TOURISM. THE CASE OF ORADEA CITY, ROMANIA - TRIP, Diana Teodora; FAGADAR, Carmen Florina; BADULESCU, Daniel; BADULESCU, Alina (Revista de turism - studii și cercetări în turism, 2021)
The commitment of smart cities to technology, sustainability, innovation, or accessibility could become an element of differentiation in the case of urban, cultural, and leisure tourism. An important part of tourists wants to find in these destinations, new things and experiences, as well as modern goods and services, comfortable and familiar, to make easy and inspiring choices. The smart tourism development of cities can also meet the requirements of economic and environmental sustainability - local businesses, sustainable and profitable, respectively, alleviating mass tourism, conservation of environment and heritage, ensuring the quality of life of tourists and residents alike. In the present study, we aimed to build an image of the smart city based on European experiences and best practice in urban tourism. Then, we interpret this knowledge and practices through the efforts made by an EU member state, especially within a city interested in such an option, in this case Oradea, Romania. We assert that the integration of tourism in this city’s long-term development strategies considers that technologies implemented in smart tourism destinations respond to important tourism challenges through accessibility, sustainability, digitization, and cultural-creative projects.